2021
DOI: 10.24251/hicss.2021.727
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Requirements for Agile Enterprise Architecture Management: A Multiple-Case Study

Abstract: Agile enterprise architecture management (EAM) is a means to cope with the pressure for continuous architectural change in the context of short innovation cycles. However, the literature states a lack of practical EAM approaches. Therefore, this study aims at fostering the development of agile enterprise architecture frameworks (EAFs) by providing agile requirements and implementation concepts based on a literature review and an exploratory multiple-case study in three organizations of the logistics and constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In a multiple-case study, Cammin et al (2021) assess the requirements for agile EAM. They identified a number of requirements that are necessary to enable agile EAM in organizations.…”
Section: Enterprise Architecture Managementmentioning
confidence: 99%
“…In a multiple-case study, Cammin et al (2021) assess the requirements for agile EAM. They identified a number of requirements that are necessary to enable agile EAM in organizations.…”
Section: Enterprise Architecture Managementmentioning
confidence: 99%
“…23 Artifacts created by the agile enterprise architecture will be always accessible and reflect the complete picture that needs to be communicated to GDAD teams for execution. 75 Team members can be assisted by agile enterprise architecture throughout the development process. PE reported that: "create the complete image, making sure it moves in the right direction.…”
Section: Agile Enterprise Architecture Usage Patternsmentioning
confidence: 99%
“…PG stated that agile enterprise architecture is: “…very much alignment.” Agile enterprise architecture is also a map that retains all troops on the same page 23 . Artifacts created by the agile enterprise architecture will be always accessible and reflect the complete picture that needs to be communicated to GDAD teams for execution 75 . Team members can be assisted by agile enterprise architecture throughout the development process.…”
Section: Research Findingsmentioning
confidence: 99%